Potential of telecommuting for different employees in the Indian context beyond COVID-19 lockdown. (September 2021) - Nayak, Suchismita; Pandit, Debapratim
Abstract: During the last decade, telecommuting has become quite popular whereas, in developing countries like India, this phenomenon is limited to a select group of employees due to various factors. The COVID-19 pandemic, the nationwide lockdown and the subsequent new normal scenario, has made the adoption of telecommuting by different type of employees indispensable thus giving us the opportunity to conduct empirical research towards understanding the factors influencing telecommuting adoption, productivity and activity-travel behaviour during telecommuting in India. The data used in this survey has been collected in two phases to capture the evolving situation of the pandemic. The analysis has been done based on revealed preference data considering three time periods i.e., before COVID-19, during COVID-19 nationwide lockdown, after the termination of the lockdown (after first wave) and for the post-COVID 19 scenario where stated preferences are considered. In the first step, telecommuting behaviour, activity-travel pattern during telecommuting and productivity is estimated based on aggregate sample data for various socio-economic groups for the period before and during COVID-19 (1. during lockdown 2. during new normal). Next, factors influencing telecommuting adoption and productivity are determined which has been used in our stated preference survey conducted in the second phase. A logistic regression model has been developed to test the association of existing telecommuting behaviour, activity-travel pattern, factors influencing productivity, socio-economic characteristics and occupation categories with future telecommuting adoption. The findings of this research can not only provide insights to urban planners and policymakers to design sustainable travel demand management strategies but can also help employers to design appropriate telecommuting strategies at the organization level which will help to attain the desired productivity levels. Our empirical analysis reveal two major findings, i.e., a large percentage of employees can achieve their desired productivity by working from home and the 'rebound' effect as identified in literature seems to have little impact in the Indian context. The novelty of this research lies in the comprehension of the adoption process, and the behavioural analysis including adoption, productivity, activity, and travel of telecommuters in the context of a developing country for the first time. Highlights: Telecommuting behavioural analysis for different employees in India. Impact of COVID-19 on telecommuting behaviour. Identification of multiple factors facilitating and hindering telecommuting. Impact of telecommuting on the activity-travel pattern. Determination of potential telecommuters in India.